Evaluasi Kinerja dan Pemilihan Supplier Menggunakan Metode Analytical Hierarchy Process (AHP): Studi Kasus di PT. Indo-Rama Synthetics Tbk - Yulianto, Dwi; Padmakusumah, Rizal Ramdan (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research aims to provide a framework for PT. Indo-Rama Synthetics Tbk in making a decisive and confident supplier selection, based on the evaluation of supplier performance. Furthermore, the study seeks to identify the key criteria that form the foundation for supplier selection within the company. The research employs the Analytical Hierarchy Process (AHP) method, with data analysis supported by Expert Choice software. The analysis reveals that the most prioritized criteria are flexibility and responsiveness (0.208), followed by compliance with POs/contracts (0.206), price (0.182), product quality (0.164), environmental friendliness and sustainability (0.162), and experience and expertise (0.077). According to the AHP results, the top supplier for the primary supply of plastic bags and rolls is Supplier PB2, which has the highest weight of 0.388. Supplier PB3 ranks second as an alternative, with a weight of 0.327, while Supplier PB1 is the third alternative, with a weight of 0.285. This research provides a clear framework for the company in selecting suppliers based on measurable performance and sustainability, which can contribute to stronger long-term relationships and improved supply quality.